A Socio-Anthropological Characterization of Sign Language Interpreters in Colombia - Salas Picón, Wilson Miguel; Galván Acosta, Francy Elena; Moreno Correa, Julio César; Corzo Colón , Libardo (Íkala, Revista de Lenguaje y Cultura, 2024)
In Colombia, sign language interpreters are needed to provide different services to deaf people, thus guaranteeing their access to fundamental rights. However, no studies have been carried out on a profile of people working as mediators/interpreters between Colombian sign language (LSC, as per its initials in Spanish) and the varieties of Spanish spoken in different regions of this country. To fill this gap, a descriptive study was carried out by applying a survey to 138 Colombian interpreters, which allowed to identify a set of characteristics related to their work, such as the time and place where they began working as interpreters, their training, employment status and income, use of digital mediation, perception of prestige and security, and membership in interpreter associations. Results show that working as an interpreter involves some risks in the areas of job stability, income and quality of life, which may linked to interpreters taking on other activities to earn enough income to sustain themselves and cover their basic needs. These findings pave the way for policy making aiming to improve interpreters’ work conditions and quality of life.